Pengaruh E-Service Quality dan Perceived Value Terhadap Repurchase Intention Dengan Customer Satisfaction Sebagai Variabel Mediasi Pada Bisnis E-Commerce - Wiryana, Novandy Yusanida; Erdiansyah, Rezi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to determine the effect e-service quality and perceived value on repurchase intention through customer satisfaction as a mediating variable in e-commerce business. The research was conducted quantitatively through survey method as many as 165 respondents toward customer at least had made transactions with e-commerce in West Jakarta Region. The sampling method uses non probability such as purposive sampling. The method of data collection is done by distributing questionnaries online and processing data uses SPSS and LISREL 8.70 for structural equation model (SEM). The result of the research hypothesis show that e-service quality, perceived value and customer satisfaction have a positive and significant effect on repurchase intention and customer satisfaction madiates the effect of e-service quality and repurchase intention on repurchase intention.